Environmental policy and innovation: a decade of research - David Popp (Center for Economic Studies and ifo Institute (CESifo), 2019)
Encouraging innovation is an important part of environmental policy. A large literature in environmental economics examines the links between environmental policy and innovation. This paper reviews recent literature on green innovation. I highlight major trends in the literature, including an increased number of cross-country studies and a focus on the effect of different policy instruments on innovation. I include a discussion of the justifications and evidence for technology-specific policy incentives and present evidence on the effectiveness of government R&D spending. My review concludes with a discussion of three promising areas for new research on environmental innovation.
Keywords: O31; O38; Q55; 330; green innovation; induced innovation; pollution; climate change; renewable energy; energy efficiency; research and development; technology policy